Architectural Mediator subunits are differentially essential for global transcription in Saccharomyces cerevisiae. Issue 3 (7th January 2021) - Tourigny, Jason P; Schumacher, Kenny; Saleh, Moustafa M; Devys, Didier; Zentner, Gabriel E
Abstract: Mediator is a modular coactivator complex involved in the transcription of the majority of RNA polymerase II-regulated genes. However, the degrees to which individual core subunits of Mediator contribute to its activity have been unclear. Here, we investigate the contribution of two essential architectural subunits of Mediator to transcription in Saccharomyces cerevisiae . We show that acute depletion of the main complex scaffold Med14 or the head module nucleator Med17 is lethal and results in global transcriptional downregulation, though Med17 removal has a markedly greater negative effect. Consistent with this, Med17 depletion impairs preinitiation complex (PIC) assembly to a greater extent than Med14 removal. Co-depletion of Med14 and Med17 reduced transcription and TFIIB promoter occupancy similarly to Med17 ablation alone, indicating that the contributions of Med14 and Med17 to Mediator function are not additive. We propose that, while the structural integrity of complete Mediator and the head module are both important for PIC assembly and transcription, the head module plays a greater role in this process and is thus the key functional module of Mediator in this regard.